2003
DOI: 10.1111/j.1467-842x.2003.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Late HIV presentation among AIDS cases in Australia, 1992–2001

Abstract: Objective: To describe time trends and demographic, exposure and clinical factors associated with late HIV presentation among notified AIDS cases diagnosed in Australia in 1992–2001. Methods: AIDS cases, diagnosed in Australia and notified to the National AIDS Registry, were included in the analysis. AIDS cases newly diagnosed with HIV infection within three months of AIDS diagnosis were defined as cases of late HIV presentation. Results: The percentage of AIDS cases with late HIV presentation increased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Previous studies in several countries have identified variables positively associated with late HIV testing or delayed diagnosis including: heterosexual transmission [2][3][4]6,13,14 ; male gender 4,5,7,15 ; both older 2,4,5,7,[16][17][18][19] and younger 3,13,20 age; foreign-born status [3][4][5][6]13 ; belonging to racial=ethnic minority populations 14,20 ; residing in areas with lower AIDS incidence 3,5 ; being less educated 16,20 ; and having tested negative for HIV prior to the first positive HIV test. 20 Whether these or other factors are correlated to late HIV testing in the San Diego-Tijuana region is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in several countries have identified variables positively associated with late HIV testing or delayed diagnosis including: heterosexual transmission [2][3][4]6,13,14 ; male gender 4,5,7,15 ; both older 2,4,5,7,[16][17][18][19] and younger 3,13,20 age; foreign-born status [3][4][5][6]13 ; belonging to racial=ethnic minority populations 14,20 ; residing in areas with lower AIDS incidence 3,5 ; being less educated 16,20 ; and having tested negative for HIV prior to the first positive HIV test. 20 Whether these or other factors are correlated to late HIV testing in the San Diego-Tijuana region is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite the benefits of timely identification of HIV infection, little or no progress has been made in effecting earlier diagnoses. [2][3][4][5][6][7] Mexico is a country with an HIV prevalence of 0.3%, 8 which is lower than its neighboring countries (i.e., Belize, 2.0%; Guatemala, 1.0%; Honduras, 1.6%; United States, 0.6%). 9 However, HIV=AIDS rates vary widely across the country.…”
Section: Introductionmentioning
confidence: 99%
“…12 All HIV cases diagnosed by State reference laboratories are reported to State health departments and are subsequently registered with the NHD. 13 …”
Section: Methodsmentioning
confidence: 99%
“…In Papua New Guinea, males and females are equally likely to become infected, with the risk of infection growing among young women (Coghlan et al, 2009;National AIDS Council Secretariat, 2008 In Australia, the proportion of AIDS diagnoses that occur around the time of HIV diagnosis rose from 31% in 1997 to 56% in 2006 (Department of Health and Ageing, 2008). Individuals with heterosexually acquired HIV infection or who were born in Asia are most likely to be diagnosed late in the course of infection in Australia (McDonald et al, 2007;Körner, 2007).…”
Section: Diverse Epidemiological Patternsmentioning
confidence: 99%